Problematika implementasi standar kompetensi lulusan dalam meningkatkan mutu pembelajaran PAI: Studi kasus di SD Islam Terpadu Al Ummah - Lutfi Firdaus; Mutthohharoh Mutthohharoh (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2026)
The implementation of Graduate Competency Standards in Integrated Islamic Schools faces challenges in integrating national education standards with distinctive Islamic educational standards. This study aims to analyze the problems of GCS implementation in improving the quality of Islamic Religious Education learning through a case study at SDI Al Ummah Jombang. This research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that GCS implementation is carried out through the integration of national standards and JSIT-specific standards. The main problems include limited use of diagnostic assessment in planning, heterogeneous student abilities and limited learning resources in implementation, and the dominance of cognitive assessment in evaluation. The study concludes that improving the quality of Islamic Religious Education learning requires data-based planning, differentiated learning, authentic assessment, and stronger collaboration between schools and parents.